1988
DOI: 10.1111/j.1365-2621.1988.tb00594.x
|View full text |Cite
|
Sign up to set email alerts
|

Heat transfer coefficient for nitrogen droplets film‐boiling on a food surface

Abstract: A method of measuring heat transfer rates from a solid food surface to liquid nitrogen droplets on it has been developed using 0.5 sec repeat-shot photography. Droplet diameters were varied from 0.1 to 2.5 mm and food surface temperatures from +30 to -100°C. All measurements were carried out at atmospheric pressure.The mean heat transfer coefficients were determined using an energy balance for the droplets. An empirical dimensionless correlation equation was established, and the significance of the results for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1989
1989
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…The heat transfer coefficient, hd to individual droplets of liquid nitrogen evaporating on a food/solid surface depends on droplet size, surface temperature of the solid and film conditions at the dropletffood interface. Awonorin and Lamb (1988) have shown that hd is approximately proportional to d-l14 and which compares well with the analytical predictions of Baumeister et al (1966) , where hd varies as d-'14 and It implies that the heat transfer rates could be enhanced by smaller droplets and lower mean temperature differences. This may be achieved by using higher pressures and substantial precooling of the products.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The heat transfer coefficient, hd to individual droplets of liquid nitrogen evaporating on a food/solid surface depends on droplet size, surface temperature of the solid and film conditions at the dropletffood interface. Awonorin and Lamb (1988) have shown that hd is approximately proportional to d-l14 and which compares well with the analytical predictions of Baumeister et al (1966) , where hd varies as d-'14 and It implies that the heat transfer rates could be enhanced by smaller droplets and lower mean temperature differences. This may be achieved by using higher pressures and substantial precooling of the products.…”
Section: Discussionsupporting
confidence: 86%
“…Schoessow, Chmielewski and Baumeister (1978) concluded that contamination of nitrogen by ice at the early stages of droplets' formation, and convection effects account for approximately 20% of the vaporization times. Hassan (1981), Awonorin (1982), and Awonorin and Lamb (1988) measured vaporization times and heat transfer to liquid nitrogen droplets on a food surface and showed decreased vaporization times, and hence, high heat transfer coefficients. The heat transfer coefficient to individual droplets contacting a solid surface (metal or food) varies with droplet diameter (d-1'4) (Baumeister etal., 1966;Awonorin & Lamb, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…However, the focus of studies was majorly on the prediction of freezing times using different models and dynamics of the freezing process, where prediction of what is happening inside the food products was missing. Heat transfer coefficient between LN 2 droplets or spray and a model food (gelatin slab) has been reported based on experimental data of evaporation rates (Awonorin & Lamb, 1988); nevertheless, the conditions considered were not similar to cryogenic freezing. As per the knowledge, the study in complex zones having nozzle and fan in IQF and (or) cryogenic freezers are not addressed adequately.…”
Section: Introductionmentioning
confidence: 99%